Depressive symptoms in adolescence: the association with multiple health risk behaviors - Katon, Wayne (2010)
OBJECTIVE: Although multiple studies of adolescents have examined the association of depression with individual health risk behaviors such as obesity or smoking, this is one of the few studies that examined the association between depression and multiple risk behaviors. METHODS: A brief mail questionnaire, which screened for age, gender, weight, height, sedentary behaviors, physical activity, perception of general health, functional impairment and depressive symptoms, was completed by a sample of 2291 youth (60.7% response rate) aged 13–17 enrolled in a health care plan. A subset of youth who screened positive on the two-item depression screen and a random sample of those screening negative were approached to participate in a telephone interview with more in-depth information obtained on smoking and at-risk behaviors associated with drug and alcohol use. RESULTS: Youth screening positive for high levels of depressive symptoms compared to those with few or no depressive symptoms were significantly more likely to meet criteria for obesity, had a poorer perception of health, spent more time on the computer, got along less well with parents and friends, had more problems completing school work and were more likely to have experimented with smoking and a wide array of behaviors associated with drug and alcohol use. CONCLUSIONS: Because many adverse health behaviors that develop in adolescence continue into adulthood, the association of depressive symptoms with multiple risk behaviors and poor functioning suggest that early interventions are needed at an individual, school, community and primary care level.